Іnfluence of technological conditions of CdTe:v crystals on their equilibrium characteristics - Парфенюк, Орест Архипович; Курик, Андрій Онуфрійович; Ілащук, Марія Іванівна; Гавалешко, Наталія Миколаївна; Чупира, Сергій Миколайович (Eastern-European Journal of Enterprise Technologies, 2014)
The equilibrium characteristics of conductivity s(Т) and Hall coefficient RH(Т) were researched in temperature region of 290 – 430 К for CdTe:V single crystal. Samples under study were taken from different parts of the ingots grown by vertical Bridgman technology from synthesized material with stoichiometric content in thermodynamic equilibrium conditions of the phases. The ingots had various impurity concentrations in the melt ( 5·1018 and 1·1019 сm-3) and different cooling speed after the growth (500 К·hour-1and 50 К·hour-1). The grown material was semi-isolating with n-type conductivity (ρ300К @2·109-1·1010 Ω·сm), rather homogeneous along the ingot, but electron Hall mobility decreased towards the upper part of it. Electric parameters of the samples which were cooled more quickly after the growth did not change after the measuring cycle. Heating of slowly cooled crystals was accompanied by irreversible changes by increase of free carriers concentration and decrease of mobility. The cause of the observed changes may be additional generation of defects of acceptor type during heating which affects the compensation conditions.